One-trial tolerance to the effects of chlordiazepoxide on the elevated plus maze may be due to locomotor habituation, not repeated drug exposure. - Dawson, G; Crawford, S; Stanhope, K; Iversen, S; Tricklebank, MD (1994)
The phenomenon of "one-trial tolerance" to the effects of chlordiazepoxide hydrochloride (CDP) in the elevated plus maze was re-examined. Unlike previous experiments, pre-exposure to the maze resulted in habituation and a consequential reduction in time spent on the open arms. The habituation effect was measured by recording the actual distance travelled by the rats in the maze and this was found to be significantly reduced by pre-exposure. Pre-exposure to the maze in the presence of CDP resulted in a reduced response to its "anxiolytic-like" effects (increasing time on the open arms compared to vehicle control rats). However, although the time spent on the open arms was reduced by pre-exposure, CDP significantly increased the time spent on the open arms by rats pre-exposed under a non-drugged state. These results suggest that rats do not become tolerant to the effects of CDP, but rather the reduced response to CDP after pre-exposure is due to habituation of exploratory behaviour.